History and culture of the Tai- Khamti - Chow Chandra Mantche (New Delhi : Aayu Publication, 2020)
Chow Chandra Mantche's "History and Culture of The Tai-Khamtis" is a significant contribution to the study of Theravada Buddhist communities in Northeast India, offering the first comprehensive examination of the Tai-Khamtis of Arunachal Pradesh. This work meticulously details their origins, migration, socio-cultural structures, economic practices, and religious beliefs, while also exploring their historical interactions with the Ahoms and the British. Mantche, drawing from his extensive experience and deep understanding of the community, bridges a critical gap in the existing literature, providing valuable insights into the cultural and historical linkages between Northeast India and Southeast Asia. This book serves as an essential resource for students, researchers, and anyone interested in the rich tapestry of Theravada Buddhism and the diverse cultural heritage of Northeast India.
Includes glossary, bibliographical references (p. 199-210).
Keywords: Tai-Khamti history and culture; Theravada Buddhism in Northeast India; Arunachal Pradesh Demographics and Geography; Historical Relations: Tai-Khamti, Ahoms, and British; Research and scholarship on Northeast Indian ethnic communities